Design of Mobile-Based Parent-Student Contribution Payment Information System - Hardi, Ica Maika; Supriadi, Supriadi (Knowbase : International Journal of Knowledge in Database, 2023)
The background for this research is that schools are still manually processing payments for student parental contributions, which requires a lot of paper, resulting in many inaccuracies in collecting data on student parental contribution payments. this causes the process of paying parental contributions to be ineffective and inefficient, so it is necessary to have an information system for paying parental contributions at SMAN 12X11 Enam Lingkung. The research method used is the Research and Development (R&D) research method, which is a method for creating a product, The System Development Life Cycle (SDLC) is a model for developing this system and implementing it using the waterfall model which consists of communication, planning, modeling, coding, and Deployment. Based on the results of the research that the authors conducted, the authors were able to create an information system for paying student donations based on PHP as a programming language and MySQL as a database at SMAN 12X11 Enam Lingkung.